The Support of Sharia Rural Banks Financing on National Financial Inclusion - Nenny Ariani; Etna Nur Afri Yuyetta; Pancawati Hardiningsih (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
The purpose of this study is to examine the effect Sharia Rural Banks Financing through Micro Small Medium Entreprise (MSMEs) financing on Financial Inclusion in Indonesia from 2011 to 2018. The study samples consists of Financial Reporting of Sharia Rural Bank from the Indonesian Financial Service Authority and Financial Inclusion from Growth Economi Report of Indonesia Central Bank. This study uses a quantitative approach with secondary Financial Inclusion data as measured by MSME Business Expansion Credit and Gross Domestic Product (GDP) using linear regression method to test the effect of variables.The results show that Sharia Rural Banks Financing has a significant effect to GDP (Gross Domestic Product) as a Financial Inclusion in Indonesia. The results of the study also showed that MSMEs Financing in Sharia Rural Banks did not have a significant relationship with Net Expansion credit because of Internal inhibiting the development of MSMEs such as low human resources, organizational management, addition limitations information technology and creativity